2018
DOI: 10.1371/journal.pone.0196725
|View full text |Cite
|
Sign up to set email alerts
|

Gear and survey efficiency of patent tongs for oyster populations on restoration reefs

Abstract: Surveys of restored oyster reefs need to produce accurate population estimates to assess the efficacy of restoration. Due to the complex structure of subtidal oyster reefs, one effective and efficient means to sample is by patent tongs, rather than SCUBA, dredges, or bottom cores. Restored reefs vary in relief and oyster density, either of which could affect survey efficiency. This study is the first to evaluate gear (the first full grab) and survey (which includes selecting a specific half portion of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 29 publications
0
20
2
Order By: Relevance
“…Dredges provide a low-cost, rapid method for assessing oyster populations, but dredge-estimated oyster densities can be affected by several factors (e.g., tow speed, line length, dredge width, etc. ), leading to dredges being labelled as unreliable tools for accurate oyster surveys (Schulte et al, 2018). However, dredge-estimated oyster densities were often less variable than quadrat-estimated densities in this study, which can be attributed to the fine-scale (< 10 m) spatial homogeneity that is not detected by the larger area sampled by an oyster dredge.…”
Section: Discussionmentioning
confidence: 63%
“…Dredges provide a low-cost, rapid method for assessing oyster populations, but dredge-estimated oyster densities can be affected by several factors (e.g., tow speed, line length, dredge width, etc. ), leading to dredges being labelled as unreliable tools for accurate oyster surveys (Schulte et al, 2018). However, dredge-estimated oyster densities were often less variable than quadrat-estimated densities in this study, which can be attributed to the fine-scale (< 10 m) spatial homogeneity that is not detected by the larger area sampled by an oyster dredge.…”
Section: Discussionmentioning
confidence: 63%
“…Chai et al (1992) found that density estimates from divers and hydraulic patent tongs were not significantly different (i.e., 100% hydraulic patent tong efficiency) and that average densities derived from each gear type were similar. Our estimated hydraulic patent tong efficiency was also lower than that of Schulte et al (2018), who compared mechanical patent tongs, which use a spring to close instead of hydraulics, to FIGURE 3. Estimated box natural mortality rates (%) by site for restored oyster reefs sampled by diver and hydraulic patent tongs in Harris Creek, Maryland.…”
Section: Discussionmentioning
confidence: 68%
“…For this approach to provide unbiased estimates of density, both sampling methods must collect and retain all eastern oysters in the area sampled. Previous studies have evaluated the efficiency of mechanical patent tongs (Schulte et al 2018) and hydraulic patent tongs relative to divers and dredges (Chai et al 1992). The results of these studies differed, with Schulte et al (2018) finding that the efficiency of mechanical patent tongs was about 76% (i.e., 76% of the oysters caught in the sample area were captured by the gear) and Chai et al (1992) finding no significant difference between divers and hydraulic patent tongs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fast-growing and abundant benthic species such as seagrasses, macroalgae, and bivalves can be destructively sampled by extractive (manual or excavating) methods for further examination, including taxonomic identification and determining biomass and biomarker levels (Molina Hernández & van Tussenbroek, 2014;Schulte, Lipcius, & Burke, 2018;Tsiamis et al, 2013). Extractive methods can also be used to sample slow-growing species where visual census methods are not feasible, such as in turbid waters (Moura et al, 2016).…”
Section: Survey Methods Considerations and Selectionmentioning
confidence: 99%